Children’s Environmental Health Indicators in Context of the Sustainable Development Goals for Small Island Developing States - Jung, Eun Mi (Int J Environ Res Public Health, 2018)
The unique environmental vulnerability of small island developing states (SIDS) is likely to impact negatively on children’s health. Children’s environmental health indicators (CEHI) are standardized measures that can be used to assess the environmental exposures and their resulting health outcomes in children. This study sought to utilize the United Nations (UN) global Sustainable Development Goals (SDGs), with their associated targets and indicators, as a framework for a CEHI proposal for SIDS. Exposure-side indicators were taken from key themes from the 2012 Rio+20 UN Conference on Sustainable Development, and health-side indicators were selected based on the most significant contributors to the burden of disease in children. The multiple-exposures–multiple-effect (MEME) framework was then used to show the relationships between environmental exposures and children’s health outcomes. The framework was populated with available data from the World Bank’s DataBank. Whilst there was some data available at a population level, major gaps in both exposure-side and health-side indicators were revealed. In order to progress children’s environmental health in SIDS, a further piece of work is required to propose a fully prioritized set of exposure-side and health-side CEHIs; based on, but not exclusively linked to, the SDGs.